Guiding Elastic Rods With a Robot-Manipulated Magnet for Medical Applications - Kratchman, Louis B.; Bruns, Trevor L.; Abbott, Jake J.; Webster, Robert J. (IEEE transactions on robotics, 2017)
Magnet-tipped, elastic rods can be steered by an external magnetic field to perform surgical tasks. Such rods could be useful for a range of new medical applications because they do not require either pull wires or other bulky mechanisms that are problematic in small anatomical regions. However, current magnetic rod steering systems are large and expensive. Here, we describe a method to guide a rod using a robot-manipulated magnet located near a patient. We solve for rod deflections by combining permanent-magnet models with a Kirchhoff elastic rod model and use a resolved-rate approach to compute trajectories. Experiments show that three-dimensional trajectories can be executed accurately without feedback and that the system's redundancy can be exploited to avoid obstacles.